Carbon nanomaterials induce residue degradation and increase methane production from livestock manure in an anaerobic digestion system. (10th December 2019) - Hao, Yi; Wang, Yaya; Ma, Chuanxin; White, Jason C.; Zhao, Ziqian; Duan, Cheng; Zhang, Yiluo; Adeel, Muhammad; Rui, Yukui; Li, Guoxue; Xing, Baoshan
Abstract: The present study investigated effects of two carbon-based nanomaterials, multiwall carbon nanotubes and fullerenes, on biogas and methane yield from sheep manure in an anaerobic digestion system over a 45 days period. The results show that the presence of 500 mg/kg multiwall carbon nanotubes or fullerenes increased the daily and accumulative production of methane (by approximately 46.8% and 33.6%), and decreased the total solid content (by approximately 12.8% and 10.4%) and pH. Exposure 50 mg/kg carbon-based nanomaterials had no impact on digestion. A high-throughput sequencing technique was used to analyze the microbial community diversity and composition in the digests across all treatments. The addition of 500 mg/kg fullerenes and multiwall carbon nanotubes notably altered the composition of the bacteria and archaea at the genus level. The change was particularly evident for Methanobacterium, whose relative abundance was significantly increased (by 67%, 53% and 120% upon with 50 mg/kg fullerenes, 50 and 500 mg/kg multiwall carbon nanotubes treatments, respectively), highlighting the positive effects of carbon-based nanomaterials on microorganisms and the subsequent acceleration of methane production. These findings provide important information on the potential use of carbon-based nanomaterials in methane production via altering or tuning the composition of the bacterial and archaeal communities and have relevance for exploring the use of carbon-based nanomaterials in clean energy and agricultural water recycling. Highlights: 500 mg/kg CNMs significantly increased the daily and accumulative methane production. The addition of 500 mg/kg CNMs caused a significant decrease in TS content. High dose of CNMs altered the abundance of Bacteroidetes, Methanobacteria, and Methanobacterium. High dose of CNMs notably altered the composition of the bacteria and archaea at the genus level.